Concentrations, sources, and biological consumption of acrylate and DMSP in the tropical Pacific and coral reef ecosystem in Mo’orea, French Polynesia - Xue, Lei; Kieber, David J.; Masdeu-Navarro, Marta; Cabrera-Brufau, Miguel; Rodríguez-Ros, Pablo; Gardner, Stephanie G.; Marrasé, Cèlia; Simó, Rafel (Frontiers in Marine Science, 2022)
Shallow-water coral reefs hold large quantities of acrylate and its precursor dimethylsulfoniopropionate (DMSP), but production and removal processes for these compounds are poorly characterized. Here we determined the concentrations and cycling of acrylate and DMSP in a transect from a coral reef ecosystem to the open ocean, 2 km beyond the reef in Mo’orea, French Polynesia, during April 2018. Concentrations of dissolved acrylate and DMSP were low throughout the reef-ocean transect, ranging from 0.8–3.9 nM and 0.2–3.0 nM, respectively, with no difference observed between the coral reef and open ocean when comparing mean concentrations (± std dev) of dissolved acrylate (1.7 ± 0.7 vs 2.3 ± 0.8 nM) or DMSP (0.9 ± 0.7 vs 1.3 ± 0.6 nM). In the coral reef, dissolved acrylate was rapidly taken up by the heterotrophic community with a fast turnover time averaging 6 h, six times faster than in the open ocean, and nearly as fast as the average turnover time of dissolved DMSP ( 3 h). A clear diel trend was observed for the heterotrophic consumption of dissolved acrylate and DMSP in the coral reef, with higher uptake rate constants during daylight hours, synchronized with the larger daytime release of acrylate and DMSP from the coral compared to the nighttime release of these compounds. We also measured photochemical production rates of acrylate in Mo’orean waters, but rates were one to two orders of magnitude slower compared to its rates of biological consumption. Coral and macroalgae were the main sources of dissolved acrylate and DMSP to the reef ecosystem. Our results indicate there is rapid turnover of acrylate and DMSP in the coral reef with a tight coupling between production and removal pathways that maintain dissolved concentrations of these two compounds at very low levels. These algal and coral-derived substrates serve as important chemical links between the coral and heterotrophic communities, two fundamental components in the ecological network in coral reefs.